A Decade of Antimicrobial Resistance in Human and Animal Campylobacter spp. Isolates - Rita Barata; Maria José Saavedra; Gonçalo Almeida (MDPI AG, 2024)
Objectives: Campylobacter spp. remain a leading cause of bacterial gastroenteritis worldwide, with resistance to antibiotics posing significant challenges to treatment and public health. This study examines profiles in antimicrobial resistance (AMR) for Campylobacter isolates from human and animal sources over the past decade. Methods: We conducted a comprehensive review of resistance data from studies spanning ten years, analyzing profiles in resistance to key antibiotics, ciprofloxacin (CIP), tetracycline (TET), erythromycin (ERY), chloramphenicol (CHL), and gentamicin (GEN). Data were collated from various regions to assess global and regional patterns of resistance. Results: The analysis reveals a concerning trend of increasing resistance patterns, particularly to CIP and TET, across multiple regions. While resistance to CHL and GEN remains relatively low, the high prevalence of CIP resistance has significantly compromised treatment options for campylobacteriosis. Discrepancies in resistance patterns were observed between human and animal isolates, with variations across different continents and countries. Notably, resistance to ERY and CHL showed regional variability, reflecting potential differences in antimicrobial usage and management practices. Conclusions: The findings underscore the ongoing challenge of AMR in Campylobacter, highlighting the need for continued surveillance and research. The rising resistance prevalence, coupled with discrepancies in resistance patterns between human and animal isolates, emphasize the importance of a One Health approach to address AMR. Enhanced monitoring, novel treatment strategies, and global cooperation are crucial for mitigating the impact of resistance and ensuring the effective management of Campylobacter-related infections.